Comparison of the Degree of Conversion of Resin Based Endodontic Sealers Using the DSC Technique - Cotti, Elisabetta; Scungio, Paola; Dettori, Claudia; Ennas, Guido (European Journal of Dentistry, 2011)
Objectives: The aim of this study was to determine the degree of conversion (DC) of three resin based endodontic sealers using the DSC technique. Methods: The sealers tested were: EndoREZ (ER) (Ultradent, South Jordan, UT); EndoREZ with Accelerator (ER+A) (Ultradent, South Jordan, UT); RealSeal (RS) (SybronEndo, Orange, CA). Two LED units were used to activate the sealers: UltraLume LED 5 (Ultradent, South Jordan, UT, USA); Mini LED Satelec (Satelec Acteon Group, Mérignac Cedex, France). Samples of 4.0 mg were analyzed with a DSC 7 calorimeter (Perkin Elmer Inc., Wellesley, MA, US). Each specimen was irradiated by each lamp four times for 20 seconds at an interval of 2 mins, while the DSC 7 recorded the heat flow developed during the treatment. The degree of conversion and the kinetic curves were calculated from the values of heat developed during each polymerization. The data were statistically analysed with a Kruskal-Wallis one-way ANOVA multiple range and Student-Newman-Keuls (SNK) tests at a P value of .05. Results: Statistically significant differences were found in the degree of conversion among the sealers: ER+A showed the highest values with both lamps. Conclusions: The higher polymerization rate in resin sealers is obtained with the addition of a catalyst. (Eur J Dent 2011;5:131-138)
Keywords: Resin-Based endodontic sealer; Differential scanning calorimeter; Polymerization; Accelerator; Degree of conversion